Construction of a fundamental system of solutions of a linear finite-order difference equation - Kruglov, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We present an efficient algorithm for the construction of a fundamental system of solutions of a linear finite-order difference equation. We obtain expressions in which all elements of this system are expressed via one of its elements and find a particular solution of an inhomogeneous equation.